Safety Nets and Turning Points: Managing Collaboration and Innovation for Teacher Efficacy in Teaching Assistant Program - Alfin Mustikawan; Ahmad Rosikhul Fahmi; Moh. Aditya Hadi Saputra; Ahmad Albert Afrilsyah (Media Manajemen Pendidikan, 2026)
This study explores the managerial dynamics of the Teaching Assistant Program (TAP) in bridging the theory-practice gap for pre-service teachers. It investigates how collaboration and innovation are managed to form professional self-efficacy within an Islamic higher education context. Employing a transcendental phenomenological design, this study analyzed the lived experiences of eight pre-service teachers selected through purposive sampling. Data were gathered via in-depth interviews to 8 informants and analyzed using systematic thematic analysis. The study reveals that teacher efficacy is not a static outcome but a dynamic construction forged through the interplay of "safety nets" and "turning points." Collaboration with mentors functions as a psychological safety net that provides essential social persuasion, enabling students to take risks. Subsequently, pedagogical innovation serves as the turning point that generates authentic mastery experiences. However, the study identifies a critical managerial barrier: infrastructure disparities among partner schools often hinder this process, creating an "efficacy divide." Sustainable efficacy is further achieved through the cognitive reframing of failure from a personal burden to a professional challenge. The findings suggest that Teacher Education Institutions (LPTKs) must manage TAP not merely as an administrative placement but as a comprehensive psychological intervention. Management must standardize mentor support protocols and address facility gaps to ensure equitable professional development for all candidates.